A low-cost, environmentally friendly aqueous zinc ion battery positive electrode material and preparation method thereof

By using cheap γ-MnO2 raw materials and hydrothermal reaction low-temperature argon annealing process, a layered Birnessite δ-MnO2 material with pre-embedded K+ and oxygen vacancy was prepared, which solved the high cost, high toxicity and easy structure damage in traditional processes. The problem has achieved the preparation and performance improvement of the positive electrode material of low-cost, environmentally friendly and safe water-based zinc ion battery.

CN114552030BActive Publication Date: 2024-12-17NORTH CHINA ELECTRIC POWER UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210166839.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-23
Publication Date
2024-12-17
Estimated Expiration
2042-02-23

AI Technical Summary

Technical Problem

The preparation process of the positive electrode material of traditional water-based zinc ion battery relies on the high-cost and highly toxic raw material KMnO4, which leads to high production costs and unsatisfactory environmental friendliness. The δ-MnO2 layered structure is easily destroyed during the charge and discharge process, affecting the cycle stability. and rate performance.

Method used

Using cheap and non-toxic γ-MnO2 as raw material, the layered Birnessite δ-MnO2 material with pre-embedded K+ and oxygen vacancy was prepared through hydrothermal reaction and low-temperature argon annealing process, overcoming the high cost and toxicity of traditional processes. A big problem.

Benefits of technology

It realizes a low-cost, environmentally friendly and safe preparation of positive electrode materials for water-based zinc ion batteries, improves the structural stability and reactivity of the materials, improves the overall performance of the batteries, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114552030B_ABST
    Figure CN114552030B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of aqueous zinc ion battery materials, and specifically relates to a low-cost, environmentally friendly aqueous zinc ion battery positive electrode material, and further discloses a preparation method thereof. The preparation method of the low-cost, environmentally friendly aqueous zinc ion battery positive electrode material of the present invention adopts cheap, safe and environmentally friendly γ-MnO2 as a raw material, and uses a simple hydrothermal method to prepare K + Pre-embedded δ-MnO2 was then annealed at low temperature in argon to further create oxygen vacancies inside the material, thus synthesizing for the first time a nanostructured ... + Birnessite-type δ-MnO2, a layered cathode material with oxygen vacancies, overcomes the defects of the traditional KMnO4-based synthesis process, which is high cost, complex process and high toxicity. It has the advantages of low process cost, environmental friendliness, safety and non-toxicity, and excellent performance, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous zinc ion battery materials, and specifically relates to a low-cost, environment-friendly aqueous zinc ion battery positive electrode material, and further discloses a preparation method thereof. Background Art

[0002] With the continuous development of economy and the continuous progress of science and technology, the demand for energy is gradually increasing. However, there are three prominent problems in the development and utilization of traditional fossil energy such as coal, oil and natural gas: resource depletion, climate warming and environmental pollution. The development of renewable energy such as solar energy, wind energy and tidal energy is an inevitable trend to solve the prominent problems faced by non-renewable energy and ensure the sustainable development of mankind. Among the current energy storage devices, lithium-ion batteries are not suitable for the development needs of large-scale energy storage due to rising costs and prominent safety issues. Therefore, the development of new aqueous batteries has important practical significance.

[0003] Rechargeable aqueous zinc-ion batteries are a new type of secondary battery that has emerged in recent years. They have the characteristics of high energy density, high power density, non-toxic battery materials, low price, and simple preparation process. Aqueous zinc-ion batteries are mainly composed of four parts: positive and negative electrodes, current collectors, diaphragms, and electrolytes. Among them, the most core factor affecting the electrochemical performance of aqueous zinc-ion batteries is the positive electrode material, and how to obtain positive electrode materials with better performance is a difficult problem that researchers are trying hard to overcome. To solve this problem, the main direction of research and development of aqueous zinc-ion batteries should be to find new positive electrode materials with high capacity and wide potential window.

[0004] MnO2 nanomaterials have many special physical and chemical properties due to their special structure, which makes them have broad prospects in the application of ion sieves, molecular sieves, catalytic materials, positive electrode materials for lithium-ion secondary batteries and new magnetic materials. At present, the preparation technology of MnO2 for positive electrode of aqueous zinc-ion batteries mainly focuses on the preparation of MnO2 with 1D tunnel structure. Among them, α-MnO2 (size of about 0.46nm) has been favored by scholars due to its excellent cycle stability and rate capability and has been widely studied. However, the raw materials used are basically KMnO4, which is a toxic and hazardous controlled drug and is expensive, resulting in the problems of high production cost and unsatisfactory environmental friendliness in the synthesis process of α-MnO2 materials.

[0005] Birnessite-type δ-MnO2 is a material with a layered structure and an interlayer spacing of about 0.7nm. Compared with α-MnO2, it is theoretically more suitable for the storage and release of zinc ions. However, the layered structure of δ-MnO2 is easily destroyed during the charge and discharge process, which is not conducive to the diffusion of ions in the material matrix, resulting in poor cycle stability and rate performance. At present, there are few studies on δ-MnO2, and there are even fewer reports on the preparation of δ-MnO2 using cheaper, safer, and more environmentally friendly raw materials. For example, Xu et al. used KMnO4 as a raw material to prepare α-MnO2, which was 0.2A g -1 The discharge capacity is 210 mAh g -1 , 1A g -1 The capacity of the material was basically not attenuated after 50 cycles. Alfaruqi et al. used KMnO4 and sulfuric acid as raw materials and synthesized α-MnO2 based on the hydrothermal method. The material has a capacity of 83 mA g -1 The discharge capacity is 233 mAh g -1 , the life span after 50 cycles is 63%, the Coulomb efficiency is close to 100%, and the 1333 and 1666 mA g -1 The capacities are 43.33 and 31.48 mAh g -1 Lee et al. used KMnO4 to synthesize α-MnO2 by hydrothermal method. The material has a capacity of 10.5 mA g -1 The capacity is 205mAh g -1 , the cycle life of 30 cycles is 66%; Pan et al. used KMnO4, H2SO4, and MnSO4·H2O as raw materials and synthesized α-MnO2 based on the hydrothermal method. The material has a lifespan of 61.6 mA g -1 The capacity is 255mAh g -1 , the life of 400 cycles is 17.6%, at 616, 1540 and 3080mA g -1 The capacities are 207, 161 and 113 mAh g -1 Alfaruqi et al. prepared α-MnO2 using KMnO4 and Mn(CH3COOH)2 as raw materials. The material has a 16 mA g -1 The capacity is 323mAh g -1 , at 1666mA g -1 The lower capacity is 47.16 mAh g -1 Han et al. prepared δ-MnO2 using KMnO4 and MnSO4·H2O. The discharge capacity of this material was 120 mAh g at 12.3 mA / g. -1, the voltage platform is around 1.25V, and the cycle life is 48% after 125 cycles. It can be seen that the traditional synthesis of α-MnO2 or δ-MnO2 is mostly based on KMnO4 as raw material, and its environmental protection and economic benefits cannot be guaranteed. Therefore, it is of positive significance to develop a process for preparing δ-MnO2, a positive electrode material for aqueous zinc ion batteries, based on cheap and non-toxic γ-MnO2 as raw material. Summary of the invention

[0006] To this end, the technical problem to be solved by the present invention is to provide a method for preparing a low-cost, environmentally friendly aqueous zinc ion battery positive electrode material, the method is based on cheap and non-toxic γ-MnO2 as a raw material, has the advantages of low process cost, environmental friendliness, safety, non-toxicity and excellent performance;

[0007] The second technical problem to be solved by the present invention is to provide an aqueous zinc ion battery positive electrode material prepared by the above method.

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a low-cost, environmentally friendly aqueous zinc ion battery positive electrode material, comprising the following steps:

[0009] (1) Mix γ-MnO2 and KOH solution and keep warm for hydrothermal reaction, collect the reaction product, wash and dry it to obtain pre-embedded K + δ-MnO2, denoted as KMO, is reserved;

[0010] (2) The obtained KMO is heated up in a protective atmosphere for low temperature annealing to obtain a pre-embedded K + and δ-MnO2 with oxygen vacancies, denoted as KMO-V, are obtained.

[0011] Specifically, in step (1), the mass ratio of γ-MnO2 to KOH is 0.5-0.6:1.

[0012] Specifically, in step (1), the temperature of the hydrothermal reaction step is 150-170° C., the reaction time is 60-80 h, and preferably the reaction temperature is 160° C. for 72 h.

[0013] Specifically, in step (1), the temperature of the drying step is 70-100° C. for heating treatment for 1.5-3 hours, preferably 70° C. for heating for 2 hours for drying.

[0014] Specifically, in step (2), the temperature of the low temperature annealing step is 250-350°C, preferably 300°C for annealing.

[0015] Specifically, in step (2), the heating rate of the heating step is 3-5°C min -1 min -1 .

[0016] Specifically, in step (2), the heating treatment step is performed for 1.5-3 hours, preferably for 2 hours.

[0017] Specifically, in step (2), the protective atmosphere includes argon.

[0018] The present invention also discloses an aqueous zinc ion battery positive electrode material prepared by the method, wherein the material contains pre-embedded K + and layered Birnessite-type δ-MnO2 materials with oxygen vacancies.

[0019] The invention also discloses the use of the aqueous zinc ion battery positive electrode material in preparing an aqueous zinc ion battery positive electrode or an aqueous zinc ion battery.

[0020] The invention also discloses an aqueous zinc ion battery positive electrode or an aqueous zinc ion battery prepared from the aqueous zinc ion battery positive electrode material.

[0021] The method for preparing the low-cost and environment-friendly aqueous zinc ion battery positive electrode material of the present invention adopts cheap, safe and environment-friendly γ-MnO2 as raw material and utilizes a simple hydrothermal method to prepare K + Pre-embedded δ-MnO2 was then annealed at low temperature in argon to further create oxygen vacancies inside the material, thus synthesizing a pre-embedded K + The Birnessite-type δ-MnO2 layered positive electrode material with oxygen vacancies overcomes the defects of the traditional KMnO4-based synthesis process, which has high cost, complex process and high toxicity. It has the advantages of low process cost, environmental friendliness, safety and non-toxicity, and excellent performance, and is suitable for large-scale production.

[0022] The Birnessite type δ-MnO2 positive electrode material of the aqueous zinc ion battery of the present invention is prepared by + Pre-embedding the δ-MnO2 layered structure can expand the zinc storage channel of the material and improve its structural stability, thereby avoiding the collapse of the layered structure caused by the insertion / extraction of zinc ions during the cycle and thus causing rapid capacity decay; at the same time, by introducing oxygen vacancies, the material's electronic structure is changed while the material's reaction activity is increased, thereby improving the overall performance of the battery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0024] Figure 1XRD patterns of KMO-V, KMO, δ-MnO2-V, and δ-MnO2 prepared in Example 1 and Comparative Examples 1-3;

[0025] Figure 2 Raman spectra of KMO-V, KMO, δ-MnO2-V, and δ-MnO2 prepared in Example 1 and Comparative Examples 1-3;

[0026] Figure 3 The electron paramagnetic resonance spectra of KMO-V, KMO, δ-MnO2-V, and δ-MnO2 prepared in Example 1 and Comparative Examples 1-3;

[0027] Figure 4 The KMO-V in Example 1 at 100 mA g -1 Discharge capacity-voltage curve at the 10th cycle under current density;

[0028] Figure 5 is a rate performance curve of KMO-V in Example 1;

[0029] Figure 6 The discharge capacity decay curve of KMO-V in Example 1;

[0030] Figure 7 The KMO in Comparative Example 1 was 100 mA g -1 Discharge capacity-voltage curve at the 10th cycle under current density;

[0031] Figure 8 It is the rate performance curve of KMO in comparative example 1;

[0032] Fig. 9 It is the discharge capacity decay curve of KMO in comparative example 1;

[0033] Fig.10 The δ-MnO2-V in Comparative Example 2 was 100 mA g -1 Discharge capacity-voltage curve at the 10th cycle under current density;

[0034] Fig.11 It is the rate performance curve of δ-MnO2-V in Comparative Example 2;

[0035] Fig.12 The discharge capacity decay curve of δ-MnO2-V in Comparative Example 2;

[0036] Fig.13 The δ-MnO2 in Comparative Example 3 was heated to 100 mA g -1 Discharge capacity-voltage curve at the 10th cycle under current density;

[0037] Fig.14It is the rate performance curve of δ-MnO2 in comparative example 3;

[0038] Fig.15 This is the discharge capacity decay curve of δ-MnO2 in Comparative Example 3. DETAILED DESCRIPTION

[0039] Example 1

[0040] The method for preparing the low-cost environmentally friendly aqueous zinc ion battery positive electrode material KMO-V described in this embodiment comprises the following steps:

[0041] (1) 7.5 g of commercial γ-MnO2 and 60 ml of 4 mol / L KOH solution were mixed and placed in a 100 ml hydrothermal reactor. The mixture was heated at 160 °C for 72 h. The product was collected and cooled to room temperature. The product was washed with deionized water three times and placed in an oven at 70 °C for 2 h to obtain pre-embedded K + δ-MnO2, denoted as KMO;

[0042] (2) The obtained KMO was heated in an argon furnace at 5 °C min -1 The temperature was raised to 300 °C at a rate of 2 h for low temperature annealing, and the product was collected and cooled to room temperature to obtain a pre-embedded K + and δ-MnO2 with oxygen vacancies, denoted as KMO-V, are obtained.

[0043] Example 2

[0044] The method for preparing the low-cost environmentally friendly aqueous zinc ion battery positive electrode material KMO-V described in this embodiment comprises the following steps:

[0045] (1) Commercial γ-MnO2 and KOH were prepared into a solution of appropriate concentration according to a mass ratio of 0.5:1, and the γ-MnO2 and KOH solutions were mixed and placed in a hydrothermal reactor with a volume of 100 ml, and the hydrothermal reaction was carried out at 150°C for 80 hours. The product was collected and cooled to room temperature. The obtained product was washed with deionized water for 3 times, and placed in an oven at 100°C for 1.5 hours to obtain pre-embedded K + δ-MnO2, denoted as KMO;

[0046] (2) The obtained KMO was heated in an argon furnace at 3 °C min -1 The temperature was raised to 250 °C at a rate of 100 °C for low temperature annealing for 3 h, and the product was collected and cooled to room temperature to obtain a pre-embedded K + and δ-MnO2 with oxygen vacancies, denoted as KMO-V, are obtained.

[0047] Example 3

[0048] The method for preparing the low-cost environmentally friendly aqueous zinc ion battery positive electrode material KMO-V described in this embodiment comprises the following steps:

[0049] (1) Commercial γ-MnO2 and KOH were prepared into a solution of appropriate concentration according to a mass ratio of 0.6:1, and the γ-MnO2 and KOH solutions were mixed and placed in a hydrothermal reactor with a volume of 100 ml, and the hydrothermal reaction was carried out at 170°C for 60 hours. The product was collected and cooled to room temperature. The obtained product was washed with deionized water for 3 times, and placed in an oven at 70°C for 3 hours to obtain pre-embedded K + δ-MnO2, denoted as KMO;

[0050] (2) The obtained KMO was heated in an argon furnace at 4 °C min -1 The temperature was raised to 350 °C at a rate of 1.5 h for low temperature annealing, and the product was collected and cooled to room temperature to obtain a pre-embedded K + and δ-MnO2 with oxygen vacancies, denoted as KMO-V, are obtained.

[0051] Comparative Example 1

[0052] 7.5 g of commercial γ-MnO2 and 60 ml of 4 mol / L KOH solution were mixed and placed in a 100 ml hydrothermal reactor. The reaction was carried out at 160 °C for 72 h. The product was collected and cooled to room temperature. The product was washed three times with deionized water and placed in an oven at 70 °C for 2 h to obtain pre-embedded K + δ-MnO2, denoted as KMO.

[0053] Comparative Example 2

[0054] 7.5 g of commercial γ-MnO2 and 60 ml of 4 mol / L KOH solution were mixed and placed in a 100 ml hydrothermal reactor. The reaction was carried out at 160 °C for 72 h. The product was collected and cooled to room temperature. The product was washed three times with deionized water and placed in an oven at 70 °C for 2 h to obtain pre-embedded K + δ-MnO2, denoted as KMO;

[0055] The obtained KMO was heated in an argon furnace at 5 °C min -1 The temperature was raised to 300 °C at a rate of 2 h for low temperature annealing, and the product was collected and cooled to room temperature to obtain a pre-embedded K + and δ-MnO2 with oxygen vacancies, denoted as KMO-V;

[0056] The obtained KMO-V was immersed in 0.8 mol L -1 HNO3 for 24 h, the obtained product was washed with deionized water three times, placed in an oven and heated at 70 °C for 2 h, and cooled to room temperature to obtain a K-free +The δ-MnO2 containing oxygen vacancies is recorded as δ-MnO2-V.

[0057] Comparative Example 3

[0058] 7.5 g of commercial γ-MnO2 and 60 ml of 4 mol / L KOH solution were mixed and placed in a 100 ml hydrothermal reactor. The reaction was carried out at 160 °C for 72 h. The product was collected and cooled to room temperature. The product was washed three times with deionized water and placed in an oven at 70 °C for 2 h to obtain pre-embedded K + δ-MnO2, denoted as KMO;

[0059] The obtained KMO was immersed in 0.8 mol L -1 HNO3 for 24 h, the obtained product was washed with deionized water three times, placed in an oven and heated at 70 °C for 2 h, and cooled to room temperature to obtain a K-free + And the δ-MnO2 without O vacancies is recorded as δ-MnO2.

[0060] Experimental example

[0061] 1. Spatial structure detection

[0062] Attached Figure 1-3 The XRD spectra, Raman spectra and electron paramagnetic resonance spectra of KMO-V, KMO, δ-MnO2-V and δ-MnO2 prepared in Example 1 and Comparative Examples 1-3 are shown respectively.

[0063] By the attached Figure 1-3 The results show that the KMO-V prepared in Example 1 of the present invention is birnessite-type δ-MnO2 (JCPDS 42-1317), and the KMO-V contains a certain amount of oxygen vacancies.

[0064] By the attached Figure 1-3 The results show that the KMO prepared in Comparative Example 1 of the present invention is birnessite-type δ-MnO2 (JCPDS 42-1317), and the KMO contains substantially no or only a small amount of oxygen vacancies.

[0065] By the attached Figure 1-3 The results show that the δ-MnO2-V prepared in Comparative Example 2 of the present invention is birnessite-type δ-MnO2 (JCPDS 42-1317), and the δ-MnO2-V contains a certain amount of oxygen vacancies.

[0066] By the attached Figure 1-3 The results show that the δ-MnO2 prepared in Comparative Example 3 of the present invention is birnessite-type δ-MnO2 (JCPDS 42-1317), and the δ-MnO2 contains substantially no or only a small amount of oxygen vacancies.

[0067] 2. Electrical performance test

[0068] The above-mentioned positive electrode materials (KMO-V, KMO, δ-MnO2-V, δ-MnO2), acetylene black, and polyvinylidene fluoride (PVDF) were taken respectively, mixed in a mass ratio of 7:2:1 (0.07 g: 0.02 g: 0.01 g), put into an agate mortar, dripped 0.3-0.5 ml of n-methyl-2-pyrrolidone, ground and mixed to form a positive electrode slurry, coated on a 14 mm diameter stainless steel mesh current collector with a soft blade, and dried in an oven at 70-100 ° C in air environment for 6-10 h. The positive electrode slurry loading was 1.8-2.2 mg cm -2 , positive electrode current collector, glass fiber separator, zinc foil negative electrode, 0.2-0.25ml electrolyte (wherein, the electrolyte used for KMO-V and KMO is 2mol L - 1 ZnSO4, 0.1 mol L -1 MnSO4, 0.1 mol L -1 K2SO4 mixed solution, δ-MnO2-V, δ-MnO2 electrolyte used is 2 mol L - 1 ZnSO4, 0.1 mol L -1 MnSO4 mixed solution) and loaded with CR2032 button battery.

[0069] The LAND CT2001A measuring instrument is used to test battery activation, discharge capacity, cycle performance, high rate performance, and energy density. The test results are all based on the quality of the positive electrode active material.

[0070] 1. Discharge capacity test

[0071] The discharge capacity of button cells formed based on the above positive electrode materials (KMO-V, KMO, δ-MnO2-V, δ-MnO2) was tested respectively, and the specific steps include:

[0072] Step 1: 100mA g -1 Charge to a potential of 1.8V;

[0073] Step 2: 100mA g -1 Discharge to potential 0.8V;

[0074] Step 3: Repeat steps 1-2 until the battery discharge capacity reaches the maximum value (C max ), the corresponding number is called the activation number (N a ).

[0075] Attached Figure 4 , 7, 10 and 13 are button cells based on KMO-V, KMO, δ-MnO2-V, and δ-MnO2 at 100 mAg -1 Discharge capacity-voltage curve of the 10th cycle under current density.

[0076] From the attached Figure 4 The results show that the initial discharge voltage of KMO-V is 1.8V and the discharge capacity is 288.8mAh g -1 , Coulombic efficiency 99.88%, energy density 389.88Wh Kg -1 .

[0077] From the attached Figure 7 The results show that the initial discharge voltage of KMO is 1.75V and the discharge capacity is 210.7mAh g -1 , Coulombic efficiency 95.36%, energy density 284.45Wh Kg -1 .

[0078] From the attached Fig.10 The results show that the initial discharge voltage of δ-MnO2-V is 1.72 V and the discharge capacity is 137.5 mAh g -1 , Coulombic efficiency 92.61%, energy density 185.63Wh Kg -1 .

[0079] From the attached Fig.13 The results show that the initial discharge voltage of δ-MnO2 is 1.7 V and the discharge capacity is 103.3 mAh g -1 , Coulombic efficiency 90.15%, energy density 139.46Wh Kg -1 .

[0080] 2. High rate performance test

[0081] The button cells formed based on the above-mentioned positive electrode materials (KMO-V, KMO, δ-MnO2-V, δ-MnO2) were respectively tested for high rate performance, and the specific steps include:

[0082] Step 1: 100mA g -1 Charge to a potential of 1.8V;

[0083] Step 2: 100mA g -1 Discharge to potential 0.8V;

[0084] Step 3: Repeat steps 1-2 until the battery is charged and discharged 10 times;

[0085] Step 4: 200mA g -1 Charge to a potential of 1.8V;

[0086] Step 5: 200mA g -1 Discharge to potential 0.8V;

[0087] Step 6: Repeat steps 4-5 until the battery is charged and discharged 10 times;

[0088] Step 7: 400mA g -1 Charge to a potential of 1.8V;

[0089] Step 8: 400mA g -1 Discharge to potential 0.8V;

[0090] Step 9: Repeat steps 7-8 until the battery has been charged and discharged 10 times;

[0091] Step 10: 600mA g -1 Charge to a potential of 1.8V;

[0092] Step 11: 600mA g -1 Discharge to potential 0.8V;

[0093] Step 12: Repeat steps 10-11 until the battery is charged and discharged 10 times;

[0094] Step 13: 800mA g -1 Charge to a potential of 1.8V;

[0095] Step 14: 800mA g -1 Discharge to potential 0.8V;

[0096] Step 15: Repeat steps 13-14 until the battery charge and discharge times reaches 10;

[0097] Step 16: 1A g -1 Charge to a potential of 1.8V;

[0098] Step 17: 1A g -1 Discharge to potential 0.8V;

[0099] Step 18: Repeat steps 16-17 until the battery charge and discharge times reaches 10;

[0100] Step 19: 100mA g -1 Charge to a potential of 1.8V;

[0101] Step 20: 100mA g -1 Discharge to potential 0.8V;

[0102] Step 21: Repeat steps 19-20 until the battery is charged and discharged 10 times.

[0103] Attached Figure 5 , 8, 11 and 14 are rate performance curves of button cells based on KMO-V, KMO, δ-MnO2-V and δ-MnO2, respectively.

[0104] From the attached Figure 5 It can be seen from the results that KMO-V is 100mA g -1 Current density N a 10,200mA g -1 Discharge capacity 251.6-275.6mAh g -1 , 400mA g -1 Discharge capacity 216.7-238.7 mAh g -1 , 600mA g -1 Discharge capacity 187.5-204.5mAh g -1 , 800mA g -1 Discharge capacity 146.5-174.2mAh g -1 , 1A g -1 Discharge capacity 82.4-131.4mAh g -1 After charge and discharge cycles, 100mA g -1 The discharge capacity can still be restored to nearly 288.8 mAh g -1 .

[0105] From the attached Figure 8 It can be seen from the results that KMO is at 100mA g -1 Current density N a 10,200mA g -1 Discharge capacity 185.6-201.8mAh g -1 , 400mA g -1 Discharge capacity 151.7-173.2mAh g -1 , 600mA g -1 Discharge capacity 127.5-143.5mAh g -1 , 800mA g -1 Discharge capacity 81.1-118.3 mAh g -1 , 1A g -1 Discharge capacity 46.4-70.4mAh g -1 After charge and discharge cycles, 100mA g -1 The discharge capacity can still be restored to nearly 210.7 mAh g -1 .

[0106] From the attached Fig.11 It can be seen from the results that δ-MnO2-V at 100mA g -1 Current density Na 10,200mA g -1 Discharge capacity 118.6-132.6mAh g -1 , 400mA g -1 Discharge capacity 96.7-110.7 mAh g -1 , 600mA g -1 Discharge capacity 76.5-92.5mAh g -1 , 800mA g -1 Discharge capacity 44.1-66.7 mAh g -1 , 1A g -1 Discharge capacity 18.4-37.9mAh g -1 After charge and discharge cycles, 100mA g -1 The discharge capacity can still be restored to nearly 137.5 mAh g -1 .

[0107] From the attached Fig.14 It can be seen from the results that δ-MnO2 at 100mA g -1 Current density N a 10,200mA g -1 Discharge capacity 86.6-97.4 mAh g -1 , 400mA g -1 Discharge capacity 58.3-77.7 mAh g -1 , 600mA g -1 Discharge capacity 35.5-52.4mAh g -1 , 800mA g -1 Discharge capacity 14.1-29.4 mAh g -1 , 1A g -1 Discharge capacity 0.02-9.4mAhg -1 After charge and discharge cycles, 100mA g -1 The discharge capacity can still be restored to nearly 103.3 mAh g -1 .

[0108] 3. Cycle performance test

[0109] The button cells formed based on the above-mentioned cathode materials (KMO-V, KMO, δ-MnO2-V, δ-MnO2) were subjected to cycle performance tests, including 500 cycles and 1500 cycles; wherein:

[0110] The test was repeated 500 times. The specific steps include:

[0111] Step 1: 600mA g -1Charge to a potential of 1.8V;

[0112] Step 2: 600mA g -1 Discharge to potential 0.8V;

[0113] Step 3: Repeat steps 1-2 until the charge and discharge cycles reach 500 times.

[0114] 500 charge and discharge cycle stability Available capacity retention rate (S 500 ) to characterize:

[0115] S 500 =C 500 / C max

[0116] In the formula, C 500 Indicates 600mA g -1 The discharge capacity at the 500th cycle, C max Indicates 600mA g -1 Maximum discharge capacity;

[0117] The test was repeated 1500 times. The specific steps include:

[0118] Step 1: 1A g -1 Charge to a potential of 1.8V;

[0119] Step 2: 1A g -1 Discharge to potential 0.8V;

[0120] Step 3: Repeat steps 1-2 until the charge and discharge cycles reach 1500 times.

[0121] 1500 charge and discharge cycle stability Available capacity retention rate (S 1500 ) to characterize:

[0122] S 1500 =C 1500 / C max

[0123] In the formula, C 1500 Indicates 1A g -1 The discharge capacity at the 1500th cycle, C max Indicates 1A g -1 Maximum discharge capacity.

[0124] Attached Figure 6 , 9 , 12 and 15 are the discharge capacity decay curves of button cells based on KMO-V, KMO, δ-MnO2-V and δ-MnO2, respectively.

[0125] From the attached Figure 6It can be seen from the results that KMO-V is 600mA g -1 Next S 500 89.4% at 1A g -1 Next S 1500 It is 91.9%.

[0126] From the attached Fig. 9 It can be seen from the results that KMO at 600mA g -1 Next S 500 31.6% at 1A g -1 Next S 1500 It is 39.6%.

[0127] From the attached Fig.12 It can be seen from the results that δ-MnO2-V at 600mA g -1 Next S 500 24.7% at 1A g -1 Next S 1500 It is 28.3%.

[0128] From the attached Fig.15 It can be seen from the results that δ-MnO2 at 600mA g -1 Next S 500 12.2% at 1A g -1 Next S 1500 It is 14.4%.

[0129] In summary, the Birnessite-type δ-MnO2 positive electrode material for aqueous zinc ion batteries of the present invention is prepared by + Pre-embedding the δ-MnO2 layered structure and introducing oxygen vacancies not only changes the electronic structure of the material but also increases the reaction activity of the material, thereby improving the overall performance of the battery system.

[0130] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a low-cost, environmentally friendly aqueous zinc ion battery positive electrode material, wherein the aqueous zinc ion battery positive electrode material contains pre-embedded K + Layered Birnessite-type δ-MnO with oxygen vacancies 2 The material is prepared by the following steps: (1) Take γ-MnO 2 and KOH solution and kept warm for hydrothermal reaction, and the reaction product was collected, washed and dried to obtain pre-embedded K + δ-MnO 2 , recorded as KMO, spare; (2) The obtained KMO is heated up in a protective atmosphere for low temperature annealing to obtain a pre-embedded K + and oxygen vacancies in δ-MnO 2 , denoted as KMO-V, we get; in, In the step (2), the temperature of the low temperature annealing step is 250-350°C; the heating rate of the heating step is 3-5°C min -1 ; The low temperature annealing step lasts for 1.5-3 hours; the protective atmosphere includes argon; In the step (1), the γ-MnO 2 The mass ratio of MgO to KOH is 0.5-0.6:1; the temperature of the hydrothermal reaction step is 150-170°C, and the reaction time is 60-80h.

2. The method for preparing the low-cost, environment-friendly aqueous zinc ion battery positive electrode material according to claim 1, It is characterized in that In the step (1), the temperature of the drying step is 70-100° C. for heating treatment for 1.5-3 hours.

Citation Information

Patent Citations

  • Preparation method and application of oxygen vacancy containing manganese / sulfur dioxide composite

    CN106972168A

  • Aqueous zinc ion battery positive electrode material and matched electrolyte

    CN112886004A

  • Ternary composite electrode material, preparation method thereof and zinc ion battery

    CN113707868A

  • Doped manganese dioxide and preparation method thereof

    CN113772735A

  • Performance enhancing additives for electrochemical cells

    WO2000079622A1